Effect of crosslink density on thermal conductivity of epoxy/carbon nanotube nanocomposites. Issue 4 (22nd September 2016) - Choi, Jae Hun; Song, Ho Jun; Jung, Jin; Yu, Jin Won; You, Nam‐Ho; Goh, Munju
ABSTRACT: The effect of the polymeric crosslink density on the thermal conductivity of an epoxy nanocomposite was investigated by adding two different diamine‐functionalized multiwalled carbon nanotubes (diamine‐MWNTs) to the epoxy resin as co‐curing agents and conducting fillers. Tetramethylenediamine (TMDA)‐MWNTs resulted in an epoxy nanocomposite with a higher crosslink density than octamethylenediamine (OMDA)‐MWNTs. Interestingly, epoxy/TMDA‐MWNT nanocomposites under 1.5 wt % nanotube concentration, showed a higher thermal conductivity than an epoxy/OMDA‐MWNT nanocomposite with the same concentration of nanotubes. In contrast, for higher diamine‐MWNT concentrations (over 2.0 wt %), the thermal conductivity of the epoxy/OMDA‐MWNT nanocomposite was higher than that with TMDA‐MWNTs. We observed that for low MWNT concentrations, where a percolating network was not formed, a high crosslink density enhanced the thermal conductivity via phonon transport. However, for high MWNT concentrations, a high crosslink density hinders the formation of a percolating network and lowers the thermal conductivity. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44253. Abstract :